Validation of the photomechanical spalling test in the case of non‐linear dynamic response: Application to a granite rock. (7th July 2020) - Lukić, Bratislav; Saletti, Dominique; Forquin, Pascal
Abstract: In this paper, the use of the virtual fields method for the identification of a strongly asymmetric compression–tension response of rock‐like materials under dynamic tensile loading is investigated. The photomechanical spalling set‐up is used, which induces an indirect tensile load in a non‐balanced sample, and the inertial component of the test is directly related to the measured dynamic stress with no previous assumption on the material behaviour. This experimental method provides a direct route to identifying the material asymmetric constitutive response in compression and tension under a uniaxial stress state as well as the material non‐linear response after tensile strength is reached. To validate this approach, the entire measurement chain for the case of a post‐peak response is investigated through simulated experiments that incorporate a damage model and synthetic grid images. Finally, the method is applied to the case of granite rock, namely, a Bohus granite, as to directly measure the material asymmetric compression–tension and the softening response after peak tensile stress.